Investigation of the occurrence of pregnancy toxemia in the sheep of Sofian area of Tabriz - Ali Hassanpour (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2007)
This study was conducted to investigate the occurrence of pregnancy toxemia in the sheep of Sofian area. In this study 134 blood samples were collected randomly from pregnant ewes before and after parturition, and the mean serum concentration of glucose, betahydroxybutyric acid (BHBA), urea and calcium were measured. The mean ± SD of BHBA concentration in prepartum and postpartum periods was 0.46± 0.15 and 0.4± 0.11 mmol/l respectively. There was significant difference between these two periods (P